Evaluation of a community pharmacy-based intervention for improving patient adherence to antihypertensives: a randomised controlled trial - Lau, R.; Stewart, K.; McNamara, K.; Jackson, S.; Hughes, Jeffery; Peterson, G.; Bortoletto, D.; McDowell, J.; Bailey, M.; Hsueh, A.; George, J. (BioMed Central, 2010)
BackgroundThe majority of patients using antihypertensive medications fail to achieve their recommended target blood pressure. Poor daily adherence with medication regimens and a lack of persistence with medication use are two of the major reasons for failure to reach target blood pressure. There is no single intervention to improve adherence with antihypertensives that is consistently effective. Community pharmacists are in an ideal position to promote adherence to chronic medications. This study aims to test a specific intervention package that could be integrated into the community pharmacy workflow to enable pharmacists to improve patient adherence and/or persistence with antihypertensive medications - Hypertension Adherence Program in Pharmacy (HAPPY).Methods/DesignThe HAPPY trial is a multi-centre prospective randomised controlled trial. Fifty-six pharmacies have been recruited from three Australian states. To identify potential patients, a software application (MedeMine CVD) extracted data from a community pharmacy dispensing software system (FRED Dispense). The pharmacies have been randomised to either 'Pharmacist Care Group' (PCG) or 'Usual Care Group' (UCG). To check for 'Hawthorne effect' in the UCG, a third group of patients 'Hidden Control Group' (HCG) will be identified in the UCG pharmacies, which will be made known to the pharmacists at the end of six months. Each study group requires 182 patients. Data will be collected at baseline, three and six months in the PCG and at baseline and six months in the UCG. Changes in patient adherence and persistence at the end of six months will be measured using the self-reported Morisky score, the Tool for Adherence Behaviour Screening and medication refill data.DiscussionTo our knowledge, this is the first research testing a comprehensive package of evidence-based interventions that could be integrated into the community pharmacy workflow to enable pharmacists to improve patient adherence and/or persistence with antihypertensive medications. The unique features of the HAPPY trial include the use of MedeMine CVD to identify patients who could potentially benefit from the service, control for the 'Hawthorne effect' in the UCG and the offer of the intervention package at the end of six months to patients in the UCG, a strategy that is expected to improve retention.Trial RegistrationAustralian New Zealand Clinical Trial Registry ACTRN12609000705280